Determining the level of data sharing, and number of publications, from research databases that have been given a favourable opinion by UK research ethics committees - Samantha Trace; Mike Bracher; Simon E Kolstoe (BMJ Open)
Objective To determine data sharing and number of publications coming from research databases that have been given a favourable opinion by UK National Health Service (NHS) Research Ethics Committees (RECs).Design Cohort study.Inclusion criteria & setting All research databases listed on the UK Health Research Authority’s Assessment Review Portal (HARP) that had received a favourable ethics opinion as of January 2018.Main outcome measures Publications and data access requests are either listed on HARP or notified through subsequent email correspondence.Results Out of 354 eligible databases, 34% had granted access requests and 40% had produced at least one peer-reviewed paper or conference abstract/talk. We could not establish contact with 9% of databases, and 19% reported no access requests or publications. Only 9% of databases were up to date with all annual reports. Email responses from database owners showed a range of attitudes towards data sharing.Conclusion Less than half of research databases that have received a favourable opinion from NHS research ethics committees share their data and produce publications. There is also considerable variability in the operation of research databases and understanding of the purpose of research databases. This work was hampered by incomplete records due mainly to researchers not submitting annual reports.